Profiling women’s reality of risk and vulnerabilities in the Nigerian cassava agri-food system - Adeyemo, Temitayo A.; Nwanze-Olaosebikan, Olamide; Omitoyin, Siyanbola A. (University of Ibadan, 2023)
Study objective: Men and women experience different realities within agri-food systems. In Nigeria, as in much of sub-Saharan Africa, sociocultural constraints have deepened women’s vulnerability to risks and shocks, consequently limiting participation in economically viable agri-food chains. This study examined the cassava agri-food system in Nigeria with a view to profiling the experiences of women in terms of risks and vulnerabilities to livelihood losses. Research question: What are the risks and shocks contributing to women’s vulnerabilities within the cassava agri-food systems in Nigeria? Methodology: The study used data of 168 women in different and sometimes overlapping nodes of the cassava value chain. The classical Vulnerability as Expected Poverty measure was used to assess women’s vulnerability to risks. Key results: Women in the cassava agri-food system mainly faced covariate risks of herdsmen conflict (35%), climate shock (22%), and fluctuating market prices (16.7%), among others. Idiosyncratic shocks mainly express as death of spouse and treatment of sick family members. Result shows that up to 94% of the women were vulnerable to loss of livelihood income because of these risks and shocks. Women managed vulnerability by riskmitigation (contractual agreements, informal saving groups), risk-coping (borrowing, multiple jobs) and riskreducing (improved farm management techniques) strategies. Contribution/implication: Although women are important at various nodes of the cassava agri-food system, vulnerability to risks may reduce their potential to make significant contributions. Gender-responsive interventions to strengthen individuals and women’s groups to build vertical and horizontal networking are necessary to overcome these barriers.